Optimizaton quality of Agar Gracilaria verrucosa Seaweed with different density in extensive polyculture system - A.R, Rahim; D.R, Utami; S, Budi (International Journal of Aquatic Research and Environmental Studies, 2023)
The polyculture system was used to increase the productivity of extensive brackishwater ponds to produce optimal agar using varying densities of three commodities: milkfish, Vannamei shrimp, and Gracilaria verrucosa. This study aimed to determine the optimal density of these three commodities in extensive brackishwater ponds with a polyculture system to produce the best agar quality from G. verrucosa.The research was conducted in an extensive brackishwater pond polyculture system in Lamongan Regency. The study used a Completely Randomized Design (CRD) with three density treatments (milkfish m⁻² : Vannamei shrimp m⁻² : G. verrucosa g m⁻²) and three replicates: A (10:10:250), B (20:20:500), and C (30:30:1000). Statistical analysis was performed using one-way ANOVA (Analysis of Variance), while Tukey’s HSD (Honestly Significant Difference) and path analysis used Pearson correlation.The results showed that the best density was obtained in treatment A, which gave a significant difference compared to treatments B and C in terms of Specific Growth Rate, Absolute Weight, Absolute Length, Carbon Content, and agar yield quality of the seaweed G. verrucosa. Path analysis demonstrated that CNP nutrients and the growth of G. verrucosa had strong and very strong influences on improving the agar yield quality of G. verrucosa seaweed.
Keywords: Agar; Extensive; Gracilaria verrucosa; Density; Polyculture